Yield-related traits characterization of local upland rice cultivars originated from East and North Kalimantan, Indonesia - NUR HASANAH; SADARUDDIN SADARUDDIN; WIDI SUNARYO (Society for Indonesian Biodiversity, 2017)
Nurhasanah, Sadaruddin, Sunaryo W. 2017. Yield-related traits characterization of local upland rice cultivars originated from East and North Kalimantan. Biodiversitas 18: 1165-1172. In East and North Kalimantan, rice genetic diversities were very high. Most of the local rice cultivars existed in East and North Kalimantan, are upland rice cultivars. Unfortunately, most of those cultivars have not been optimally studied and characterized for rice breeding purposes. In this study, 146 upland rice cultivars originated from East and North Kalimantan were grown in the field which was further characterized their yield parameters. Tillering capacity, productive tiller, the size and structure of panicle as well as grain characteristics were characterized in the population to select potential superior cultivars. The results showed that the phenotypic variation of tillering capacity in those local upland rice was very high. Tiller number was varied from 2 to 66 tillers, with an average of 20.92 tillers and 25 cultivars had more than 30 tillers. Large range of productive tiller was also observed in the population, ranging from 14.8 to 100% of their tillering capacity, but most of the cultivars (80%) had more than 70% productive tiller. In addition, 9 cultivars had 100% productive tillers, in which all of the tillers generated panicles. Highly significant positive correlation (0.802**) was observed between productive tiller and tillering capacity. The panicle length of the local upland rice cultivars was in range from 14.5 cm to 43.5 cm, with most of the panicle size population clustered in length of 20-30 cm. In addition, 8.2% cultivars had a dense/heavy category, while 22.6% were sparse, and the rest of 70.2% had no panicle secondary branch. Variation of grain characteristics of local upland rice in the East and North Kalimantan including grain weight, grain length and width, as well as length-to-width ratio was also discussed in this study.